IMC Strategies of K-EXPO 2024: Localizing Korean Agro & Fisheries - Dhyana, Dharma, DD; Dewi, Helga Liliani Cakra, HLCD; Nurhayati, Kristina (UI Scholars Hub, 2026)
The global rise of the Korean Wave (Hallyu) has created a significant market for Korean products in Indonesia, one of its key export destination. While Korean food (K-Food) is popular, Korean seafood (K-Seafood) remains relatively unknown, presenting a unique marketing challenge. This study examines the Integrated Marketing Communication (IMC) strategies implemented by K-EXPO 2024 to localize and promote K-Seafood to Indonesian consumers, addressing key challenges such as low product awareness and the prevalent stereotype of K-Food being non-halal. Employing a qualitative approach, this research draws on in-depth interviews with key practitioners, including the K-EXPO 2024 Project Head and Promotion Manager, an agro-trade representative, and Indonesia's Minister of Trade. Thematic analysis reveals that the event's success stemmed from a sophisticated IMC strategy. This finding aligned with the Indonesian government's perspective that market penetration hinges on business-led promotional innovation rather than direct trade policy. The findings show that the strategy rested on three pillars: (1) strong message consistency centered on halal certification as a foundational